Radioanatomical Study of the Pedicle of the Superficial Circumflex Iliac Perforator Flap - Gentileschi, Stefano; Servillo, Maria; De Bonis, Francesca; Albanese, Roberta; Pino, Valentina; Mangialardi, Maria Lucia; Valente, Iacopo; Garganese, Giorgia; Scambia, Giovanni; Salgarello, Marzia; Cina, Alessandro (Journal of Reconstructive Microsurgery, 2019)
Background The superficial circumflex iliac perforator (SCIP) flap has many ideal features, such as fast dissection, possibility to harvest thin, pliable, wide skin island, and concealed donor site scar. In spite of these features, its use was limited because of the wide anatomical variation of the pedicle, which is relatively shorter and has a smaller caliber than other more popular perforator flaps. Several names were given to the branches and perforators in the literature, thus adding confusion to the understanding of its anatomy.Methods We performed a surgical and a radioanatomical study of the SCIP pedicles analyzing high-resolution contrast-enhanced computed tomography (CT) scan of 95 groins, with particular attention to the deep branch (DB) of the superficial circumflex iliac artery (SCIA). Twenty-three of these patients were also studied by detecting the surgical anatomy during SCIP flap harvest. We employed a system of coordinates based on the line between pubic tubercle (PT) and anterior superior iliac spine (ASIS) to describe the position of the perforator of the DB.Results We found a 100% correlation between surgical and radiological findings. The length of the DB from the origin to the point in which its perforator pierced the sartorius fascia ranged from 1.6 to 6.5 cm, mean = 3.62 ± 0.92 cm. The distance between the origin of the DB and the inguinal ligament ranged from 1.1 to 7.5 cm, mean = 2.8 ± 1 cm. The perforator of the DB could be found in 91% of the cases within a box of 4 cm × 3 cm drawn caudally to the line joining the PT with the ASIS. This vessel can show a vertical or horizontal course in the subcutaneous layer.Conclusion Our findings confirm other previous studies and add new information about the position and the course of the perforator of the DB of the SCIA. Important features of the SCIP pedicles can be investigated by the color Doppler ultrasound and CT scan.
Keywords: superficial circumflex iliac perforator flap; superficial circumflex iliac artery; groin flap; radioanatomical study; groin dissection; perforator flap